2021
DOI: 10.3390/jcm10122628
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial Factors Associated with Supportive Care Needs in Canadian Adolescent and Young Adult Cancer Survivors

Abstract: Adolescents and young adults (AYAs) represent an overlooked population in cancer survivorship care. Identifying the needs of AYAs can guide the development of tailored programs for this population. We conducted a cross-sectional descriptive analysis to identify biopsychosocial factors associated with AYA post-treatment supportive care needs and unmet needs using data obtained from the Experiences of Cancer Patients in Transitions Study of the Canadian Partnership Against Cancer, in collaboration with cancer ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Up till now, there is no optimal survivorship care model, and many differences (between and within countries) may exist, leaving much room for improvement and still a lot can be learned from each other (e.g., by benchmarking). Despite the emergence of AYA care programs, there is a limited number of programs with survivorship elements [1, 25,73,77,[134][135][136][137].…”
Section: Challenges and Models Of Aya Survivorship Carementioning
confidence: 99%
See 1 more Smart Citation
“…Up till now, there is no optimal survivorship care model, and many differences (between and within countries) may exist, leaving much room for improvement and still a lot can be learned from each other (e.g., by benchmarking). Despite the emergence of AYA care programs, there is a limited number of programs with survivorship elements [1, 25,73,77,[134][135][136][137].…”
Section: Challenges and Models Of Aya Survivorship Carementioning
confidence: 99%
“…In addition, many AYA survivorship issues are still poorly understood and possibly neglected [16,66,73,118,137,154]. Because both HCPs in hospitals and general practitioners (GPs) only see a limited number of AYAs in their practice, they are often unfamiliar with AYA-specific issues and have limited expertise in AYA specific care [12,46,118,136]. Being unfamiliar with this patient population may lead to the provision of suboptimal follow-up care.…”
Section: Challenges For Aya Survivorship Carementioning
confidence: 99%
“…Sex-specific prevalence by cancer types (e.g., prostate cancer, breast cancer) may also account for the sex differences in receiving an SCP. AYA patients were less likely to receive an SCP compared to adults; this is important given that previous research has found that younger patients have higher survivorship needs and less satisfied with the transition [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Optimal transitional practices should incorporate a core set of priorities that have been articulated by AYA cancer survivors. [60][61][62] These include a desire for flexible and individually tailored transitions with effective communication and continuity of providers during the transition process. 63 Previous qualitative work has highlighted survivors' desire for integration of discussions of financial hardship, fertility services, and psychosocial health into long-term care programs.…”
Section: Transition In Aya Survivorsmentioning
confidence: 99%